2013
DOI: 10.1007/s00005-013-0251-0
|View full text |Cite
|
Sign up to set email alerts
|

Lobular Breast Cancer: Pathology, Biology, and Options for Clinical Intervention

Abstract: Lobular carcinoma is a breast cancer subtype comprising approximately 15 % of all breast cancer cases. Clinical diagnosis of this subtype is difficult due to a characteristic growth pattern that inhibits detection using palpation or standard X-ray mammography. While clinical intervention based on hormone antagonists has proven an effective strategy, hormone receptor negative or nonresponsive disease cannot be treated successfully, indicating the need for alternative curative approaches. In contrast to its well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 169 publications
2
14
0
Order By: Relevance
“…In addition to the high expression of ERβ in early lobular cancer, another marked difference between lobular and ductal cancer was the lack of proliferating cells in lobular cancer: Ki67-positive cells were very abundant in ductal cancer but very rare in lobular cancer. Thus, our data support the previous conclusion (47,48) that lobular cancer is a disease resulting from resistance to anoikis and not one of proliferation. What was surprising in the present study is the finding that high-grade lobular cancer is characterized by loss of ERβ expression, high ERα level, and high proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the high expression of ERβ in early lobular cancer, another marked difference between lobular and ductal cancer was the lack of proliferating cells in lobular cancer: Ki67-positive cells were very abundant in ductal cancer but very rare in lobular cancer. Thus, our data support the previous conclusion (47,48) that lobular cancer is a disease resulting from resistance to anoikis and not one of proliferation. What was surprising in the present study is the finding that high-grade lobular cancer is characterized by loss of ERβ expression, high ERα level, and high proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Apart from the obvious EMT hallmark (E-cadherin loss), metastatic cells in these models retained their epithelial characteristics based on luminal cytokeratin expression patterns, and lacked expression of the mesenchymal EMT markers. These findings conform to clinicopathological findings in DGC and ILC, where invading cells and their metastases are luminal epithelial-type cancer cells (Vlug et al 2013a;Mahmud et al 2015;van der Post et al 2015). In sum, these data demonstrate that early mutational loss of E-cadherin does not lead to a classical EMT.…”
Section: E-cadherin Loss and The Epithelial To Mesenchymal Transitionsupporting
confidence: 86%
“…Anchorage-dependent cell growth was assessed as previously described 5 . In short, cells were grown on 12-well plates incubated with the indicated inhibitors.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent studies using mouse and human ILC models have shown that tumour progression is in part due to anchorage independence triggered by p120-catenin-dependent activation of RhoA and Rock1 3 , 4 . Loss of E-cadherin expression is observed in the vast majority of lobular breast cancers, mostly due to inactivating CDH1 mutations and subsequent loss of heterozygosity, or epigenetic silencing of the E-cadherin promoter 5 . As a result of E-cadherin inactivation, the adherens junction (AJ) is no longer functional, leading to disruption of epithelial integrity and acquisition of tumour-promoting events such as anchorage independence, angiogenesis and tumour cell invasion 6 .…”
Section: Introductionmentioning
confidence: 99%